Theoretical description of the ligand function for ionoselective electrodes reversible to metal anion complexes. 1. Lower detection limit and its determining factors - Egorov, Vladimir V.; Semenov, Andrei V.; Novakovskii, Andrei D.; Akayeu, Yauhen B. (Journal of the Belarusian State University. Chemistry, 2020)
Within the framework of the steady-state diffusion model, the theoretical description for the thiocyanate ion lower detection limit (LDL) by the tetrathiocyanatozincate selective electrode, has been presented. The main assumptions of this model are constancy of the ion exchanger concentration along the membrane, traditionally used in various phaseboundary potential diffusion models, and linear profiles of components’ concentrations in diffusion layers. Simple quantitative expressions have been obtained, connecting thiocyanate ion concentration in the solution surface layer (responsible for LDL value) with phase boundary extraction equilibria constants, stability constants for zinc thiocyanate complexes, and diffusion parameters in the membrane and solution phases. Calculated LDL values are in good agreement with experimental data provided in the literature. It has been shown that LDL can be reduced substantially by controlling such easily regulated diffusion parameters as diffusion layer thickness in the membrane phase, which is a function of time, and diffusion layer thickness of the sample solution, which is governed by stirring regime.